Integrasi Kompetensi Pelaut dalam Kurikulum Pendidikan Penerbangan: Studi Kasus Akademi Penerbang Indonesia Banyuwangi - Dede Ardian; Riki Wanda Putra2; Kukuh Tri Prasetyo; Ahmad Mubarok (Jurnal Pendidikan Indonesia, 2025)
This study examines the influence of the integration of seafarers' competencies on the performance of aviation education by adapting the curriculum as a mediating variable at the Indonesian Aviation Academy Banyuwangi. The study uses an explanatory quantitative approach with structural equation modeling analysis based on Partial Least Squares (PLS-SEM). Data collection was carried out through a questionnaire of 95 respondents consisting of cadets, instructors, and industry practitioners. The data was analyzed using SmartPLS 4 software to test the validity, reliability, and hypothetical relationships. The results of the study prove that the integration of seafarers' competencies has a significant effect on curriculum adaptation (β = 0.635; p < 0.01) and flight education performance (β = 0.274; p < 0.01). Curriculum adaptation also had a significant effect on the performance of aviation education (β = 0.615; p < 0.01) and acted as an effective partial mediator. The research model was able to explain the variation in flight education performance by 74.2% (R² = 0.742) with a substantive predictive relevance (Q² = 0.439). The integration of seafarers' competencies has been proven to improve the performance of aviation education directly or indirectly through curriculum adaptation. These findings recommend an interdisciplinary approach in the development of aviation vocational education curriculum through cross-sectoral competency integration.